ASPEK HUKUM TERHADAP GANTI RUGI PENCEMARAN MIGAS LINTAS BATAS YANG DISEBABKAN OLEH OFFSHORE ACTIVIES - Arfi Fazrian; Nurdin Nurdin (Jurnal Ilmiah Mahasiswa Bidang Hukum Kenegaraan, 2018)
Polluter Pay’s Principle, which ones of principle of compensation in international environmental law, exploitation oil and gas activities on offshore areas would be damage not only the jurisdiction of the sea areas belong to coastal states but also spread to jurisdiction of other coastal states. So that, the states which exposed damage are involving compensation to remedy the environment of the sea that tainted. The wrote Thesis has aimed to know and to explain concerning regulations and mechanism toward compensation of transboundary oil and gas pollution caused by offshore activity based on International Convention on Oil Pollution Preparedness, Response and Cooperation 1990. Convention on Civil Compensation for Oil Pollution Damage Resulting from Exploration and Exploitation of Seabed Mineral Resources 1977. Convention on Environmental Impact Assessment in a Transboundary Context 2001 and regulations in Indonesia. In order to obtain data in this wrote Thesis has been doing library research. That is to learn and to analyze the Conventions, the Regulations, text books, news paper, journal and any literate have related to this Thesis. The resulted of this Thesis explaining the regulations toward compensation of transboundary oil and gas pollution caused by offshore activities have not been be regulated definitely, because the regulations have not yet entry into force. But, The parties that wanted compensation are operator from offshore installation, whereas the claim could be propose when the activity to repair of marine environment tried to be done and together with party of origin to do study about Environmental Impact Assessment. Mechanism for giving compensation could be done with two ways, through insurance of environment and special body in this case is OPOL Association Limited. Based on the explanation, recommended to any states are studying exhaustive and doing the convention related transboundary oil and gas pollution caused by offshore Activities. Furthermore, recommended to Indonesian government is doing regional cooperation with ASEAN Countries, Asia Pacific and Australia and also ratify Espoo Convention.